ANALISIS USAHA DAN POTENSI PENGEMBANGAN KERAMBA JARING APUNG DI DESA SIKAKAP KABUPATEN KEPULAUAN MENTAWAI SUMATERA BARAT - Hendrik ' (Berkala Perikanan Terubuk, 2009)
This study aims to determine the prospects of floating net in terms of aspectsof business analysis and development potential. The results showed for eachbusiness unit developed the KJA fishing effort as a contributory factor, earned netincomeof USD44.109million per harvest (8 months) and total investmentof Rp. 118.275 million. From a variety of investment criteria can be said tobe floatingnet business is worthto bedeveloped. Soalsointhe review of potential development in the village could be developed as muchas 2382 Sikakap KJA, the current number of KJA newly developed 41 unit. Thismeans that the utilization rate of sea cages in Sikakap for development isstill less than 2%